Experimental energy, exergy, economic and exergoeconomic analyses of batch-type solar-assisted heat pump dryer - Singh, A.; Sarkar, J.; Sahoo, R.R. (Elsevier Ltd, 2020)
In the present study, a batch-type solar-assisted heat pump dryer (SAHPD) has been developed and experimented in both simple heat pump dryer (HPD) and SAHPD modes for closed system drying of banana chips. The effect of drying time on various energy, exergy, economic and exergoeconomic performance parameters has been investigated. The banana chips have been dried to remove moisture from 83.5% to 11.5% at an air velocity of 1 m/s in the drying chamber. Both energy efficiency and exergy efficiency are found higher for SAHPD. The specific moisture extraction rate is higher for SAHPD as compared to simple HPD. On the basis of economic analysis, the payback period for the SAHPD over the simple HPD is found 46 months. The lowest exergoeconomic factor is for the expansion device in simple HPD and SAHPD with determined values as 0.1395 and 0.2053, respectively. Total exergy destruction cost for simple HPD and SAHPD is 0.1185 $/h and 0.1386 $/h, respectively. It is observed that the most important components that needed to improve based on exergoeconomic factor are expansion device and evaporator. The present study reveals that the SAHPD system is much better than the simple HPD system. © 2020 Elsevier Ltd
Keywords: Solar-assisted heat pump dryer; Specific moisture extraction rate; Exergy efficiency; Exergy destruction cost rate; Exergoeconomic factor